2008
DOI: 10.5713/ajas.2008.60505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Calcium Salts of Palm Oil Fatty Acids on Performance of Lactating Crossbred Cows

Abstract: Twenty lactating crossbred cows yielding 10 to 15 litres of milk daily during mid lactation were selected and divided into four groups of five animals to assess the effect of feeding calcium soaps of palm oil fatty acids (bypass fat) on milk yield, milk composition and nutrient utilization in lactating crossbred cows. The animals in groups 1 (control), 2, 3 and 4 were fed concentrate mixture containing 0 (no bypass fat), 2, 4 and 6% bypass fat, respectively. The average daily dry matter consumption in the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 39 publications
(50 reference statements)
7
27
0
Order By: Relevance
“…Also, Purushothaman et al (2008) found that the differences in feed intake among lactating crossbred cows fed rations containing 0, 2, 4 and 6% of calcium salts of palm oil fatty acids were not significant. The nearly similarity in CFM intake in all the groups of cows in the present study could be ascribed to the fact that the added inert fat is likely to have remain largely unavailable in the rumen because of its low solubility and high melting point (Canale et al, 1990), thereby not impairing rumen fiber digestibility and avoiding an increase in gut fill that can limit dry matter intake.…”
Section: Feed Intakementioning
confidence: 92%
“…Also, Purushothaman et al (2008) found that the differences in feed intake among lactating crossbred cows fed rations containing 0, 2, 4 and 6% of calcium salts of palm oil fatty acids were not significant. The nearly similarity in CFM intake in all the groups of cows in the present study could be ascribed to the fact that the added inert fat is likely to have remain largely unavailable in the rumen because of its low solubility and high melting point (Canale et al, 1990), thereby not impairing rumen fiber digestibility and avoiding an increase in gut fill that can limit dry matter intake.…”
Section: Feed Intakementioning
confidence: 92%
“…An increase in the proportion of LCFA (C18:1, C18:2, C18:3) takes place due to more uptake of preformed LCFA from blood (Mishra et al, 2004). The supplementation of bypass fat increases milk fat in lactating cows (Fahey et al, 2002;Purushothaman et al, 2008;Rajesh, 2013;Yadav et al, 2015). These findings are in line with the present investigation.…”
Section: Resultsmentioning
confidence: 99%
“…There is also another economically valuable byproduct – calcium soap from scenarios I, III, and IV. Calcium soap can be used as a feed supplement for dairy cattle and other ruminants …”
Section: Resultsmentioning
confidence: 99%